2015
DOI: 10.1097/wnp.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Electrographic Seizure Detection by Neurophysiologists and Non-Neurophysiologists in the Adult ICU Using a Panel of Quantitative EEG Trends

Abstract: Purpose: To evaluate the sensitivity and specificity of a panel of quantitative EEG (qEEG) trends for seizure detection in adult intensive care unit (ICU) patients when reviewed by neurophysiologists and non-neurophysiologists. Methods: One hour qEEG panels (n ¼ 180) were collected retrospectively from 45 ICU patients and were distributed to 5 neurophysiologists, 7 EEG technologists, and 5 Neuroscience ICU nurses for evaluation of seizures. Each panel consisted of the following qEEG tools, displayed separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 19 publications
0
62
1
Order By: Relevance
“…Prior studies have reported similar sensitivity rates using aEEG or CDSA (15,16,3235). However, the majority of these studies evaluated the ability of neurophysiologists or neurologists to detect seizures as opposed to that of non EEG trained bedside providers.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Prior studies have reported similar sensitivity rates using aEEG or CDSA (15,16,3235). However, the majority of these studies evaluated the ability of neurophysiologists or neurologists to detect seizures as opposed to that of non EEG trained bedside providers.…”
Section: Discussionmentioning
confidence: 67%
“…However, the majority of these studies evaluated the ability of neurophysiologists or neurologists to detect seizures as opposed to that of non EEG trained bedside providers. One study that included 5 neuroscience nurses who received a 15 minute training tutorial had a sensitivity for seizure detection on CDSA and aEEG of 87%, but with a specificity of 61.6%(35). Furthermore, a study including 2 neurointensive care nurses who underwent a 5–6 hour training had a sensitivity of 92–99% and specificity of 89–90% for seizure detection on aEEG and CDSA used together (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compressed spectral arrays (CSA) are a common way to visualize EEG trends and have been used in most prior studies of the use of qEEG for seizure detection in adults (Moura et al , 2014; Williamson et al , 2014; Dericioglu et al , 2015; Swisher et al , 2015; Topjian et al , 2015). CSA is produced by applying spectral estimation techniques to continuous EEG data, thereby producing a three-dimensional compressed spectrogram with time on the x-axis, frequency on the y-axis, and EEG power on the z-axis (Bickford et al , 1972; Bricolo et al , 1978).…”
Section: Introductionmentioning
confidence: 99%
“…A handful of studies have also evaluated the sensitivity of CSA alone for detecting seizures by physicians and ICU nurses (Stewart et al , 2010; Pensirikul et al , 2013; Dericioglu et al , 2015; Swisher et al , 2015; Topjian et al , 2015). Of all members of the care team, ICU nurses have the most frequent patient interaction and are typically charged with alerting physicians to changes in vital signs, neurological status, cardiac telemetry and other monitored systems.…”
Section: Introductionmentioning
confidence: 99%